Pengaruh Senam Ergonomik Berbasis Spiritual Terhadap Perubahan Tekanan Darah Lansia Penderita Hipertensi Di Kelurahan Jebres - Indriyani Ayu Mandira; Erika Dewi Noorratri (Nursing News : Jurnal Ilmiah Keperawatan, 2022)
Physiological changes experienced by the elderly with getting older then the function of the body's organs will also decreased, such as Health problems experienced by the elderly in the cardiovascular system that result in hypertension. Hypertension is often referred to as the "silent killer" because it can appear without symptoms, so many are not aware of it. Non-pharmacological methods of handling are spiritual-based ergonomic gymnastics. exercise can improve the function of vasodilation which can reduce peripheral vascular resistance, when the elasticity of blood vessels increases, it will make it easier for blood vessels to relax quickly while the heart is pumping. To determine the effect of spiritual-based ergonomic exercise on changes in blood pressure in elderly patients with hypertension in Jebres Village. To determine the effect of spiritual-based ergonomic exercise on changes in blood pressure in elderly patients with hypertension in Jebres Village. Wilcoxon test a significant P Value (0.000 0.05). Ada pengaruh senam ergonomik berbasis spiritual terhadap perubahan tekanan darah pada lansia penderita hipertensi di Kelurahan Jebres.